![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
展开全部
(10-6)*2*3=24;(2*3-10)*(-6)=24
展开全部
(-6+10)×2×3=24
[10-(-6)÷3]×2=24
[10-(-6)÷3]×2=24
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
3*((4-6)+10)
3*(4-(6-10))
3*((4+10)-6)
3*(4+(10-6))
((3*6)-4)+10
(3*6)-(4-10)
((3*6)+10)-4
(3*6)+(10-4)
3*((10+4)-6)
3*(10+(4-6))
(3*(10-4))+6
3*((10-6)+4)
3*(10-(6-4))
4+((6/3)*10)
4+(6/(3/10))
4+((6*10)/3)
4+(6*(10/3))
((4-6)+10)*3
(4-(6-10))*3
4+((10/3)*6)
4+(10/(3/6))
((4+10)-6)*3
(4+(10-6))*3
4+((10*6)/3)
4+(10*(6/3))
6-(3*(4-10))
((6*3)-4)+10
(6*3)-(4-10)
6+(3*(10-4))
((6*3)+10)-4
(6*3)+(10-4)
((6/3)*10)+4
(6/(3/10))+4
6-((4-10)*3)
((6*10)/3)+4
(6*(10/3))+4
6+((10-4)*3)
(10+(3*6))-4
10+((3*6)-4)
((10/3)*6)+4
(10/(3/6))+4
(10-4)+(3*6)
10-(4-(3*6))
((10-4)*3)+6
((10+4)-6)*3
(10+(4-6))*3
(10-4)+(6*3)
10-(4-(6*3))
(10+(6*3))-4
10+((6*3)-4)
((10*6)/3)+4
(10*(6/3))+4
((10-6)+4)*3
(10-(6-4))*3
3*(4-(6-10))
3*((4+10)-6)
3*(4+(10-6))
((3*6)-4)+10
(3*6)-(4-10)
((3*6)+10)-4
(3*6)+(10-4)
3*((10+4)-6)
3*(10+(4-6))
(3*(10-4))+6
3*((10-6)+4)
3*(10-(6-4))
4+((6/3)*10)
4+(6/(3/10))
4+((6*10)/3)
4+(6*(10/3))
((4-6)+10)*3
(4-(6-10))*3
4+((10/3)*6)
4+(10/(3/6))
((4+10)-6)*3
(4+(10-6))*3
4+((10*6)/3)
4+(10*(6/3))
6-(3*(4-10))
((6*3)-4)+10
(6*3)-(4-10)
6+(3*(10-4))
((6*3)+10)-4
(6*3)+(10-4)
((6/3)*10)+4
(6/(3/10))+4
6-((4-10)*3)
((6*10)/3)+4
(6*(10/3))+4
6+((10-4)*3)
(10+(3*6))-4
10+((3*6)-4)
((10/3)*6)+4
(10/(3/6))+4
(10-4)+(3*6)
10-(4-(3*6))
((10-4)*3)+6
((10+4)-6)*3
(10+(4-6))*3
(10-4)+(6*3)
10-(4-(6*3))
(10+(6*3))-4
10+((6*3)-4)
((10*6)/3)+4
(10*(6/3))+4
((10-6)+4)*3
(10-(6-4))*3
参考资料: http://zhidao.baidu.com/question/70471502.html?fr=ala1
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
2 × [10-(-6 ÷ 3)] = 24
(-6+3)× (2-10)=24
(2 × 3) × (10 - 6)=24
(10 -(-6)) × 3 ÷ 2=24
(-6+3)× (2-10)=24
(2 × 3) × (10 - 6)=24
(10 -(-6)) × 3 ÷ 2=24
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
(2×3-10)×(-6)=24
(10-(-6))÷2×3=24
(10-(-6))÷2×3=24
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
2*3*(10-6)
(2-10)*(3-6)
(2-10)*(3-6)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询